Perubahan Sosial Masyarakat Di Blahbatuh Pada Tahun 1980 – 2015 - Oka Segara, Ngakan Putu; Wirawan, A.A. Bagus; Inten Asmariati, A.A. (Humanis; Volume 16. No. 3. September 2016, 2016)
Blahbatuh a district once the public village in Gianyar district that grow over time, starting from an agrarian growth evolved into a traditional trade to modern heading on tourism with various problems lead to social change in the society Blahbatuh interesting to study. The actor who made those changes is Blahbatuh society that responds to the changing times by his activity. This study uses empirical approaches are used as a way to determine the cause - the cause of social change through activities tejadinya felt capable of changing values ??within the community. The theory used in this study is twofold theory of social change through activities and theory of history based on the foundation of the soul era. This research uses descriptive qualitative research as a research procedure that produces the data descriptive and has a combined stream of the organic stream with a personal-intuitive for writing. Data collection techniques used in this study are: observation, interviews, and documentation. The results of this study concluded the causes of social change in Blahbatuh there are several factors of observers researchers for conducting research community role models that factor, the factor of information, technology factors, factors of trust, relationship factors, educational factors and factors of the economy. Social change based on factors fartor this cause but in practice (practice) is different, have the same meaning. It depends on the public's knowledge of this causal factors and also in the development of people's livelihood developing frequent development times.